Maternal urinary concentrations of bisphenol A during pregnancy and birth size in children from the Odense Child Cohort - Astrid L. Beck; Elvira V. Bräuner; Cecilie S. Uldbjerg; Youn-Hee Lim; Henriette Boye; Hanne Frederiksen; Anna-Maria Andersson; Tina Kold Jensen (Environmental Health)
Abstract Background Bisphenol A (BPA) is widely used in the manufacturing of plastics. BPA can pass the placental barrier and influence fetal development. Due to its estrogenic and anti-androgenic properties, BPA may contribute sex-specific differences in developmental effects. We examined associations between maternal urinary concentrations of BPA and birth size. Methods In this cohort study of 832 mother-child pairs from the Odense Child Cohort, pregnant women provided spot urine samples at gestational week 28, which were analyzed for BPA by isotope diluted LC-MS/MS. Osmolality adjusted urinary BPA concentrations were categorized into quartiles. Mother-child characteristics were obtained from hospital records and questionnaires. Linear regression analyses examining the association between BPA concentrations and offspring birth size (weight, length, head, and abdominal circumference) were performed for the full cohort and stratified by offspring sex. Results BPA was detected above the limit of detection in 85% of the urine samples with a median concentration of 1.33 ng/ml. In the full cohort, birth weight decreased significantly across increasing quartiles of maternal urinary BPA concentration, with the exception of the third quartile, which showed no significant association. In sex-stratified analyses, statistically significant decreases in birth weight were observed among male offspring in the highest quartile of maternal urinary BPA concentrations (β: -115 g, 95% CI: − 225, -4, p = 0.04) compared to male offspring of the lowest quartile and a possible dose-response association was suggested (p-trend = 0.06). No statistically significant associations were observed for birth weight amongst female offspring. Conclusions Our findings suggest a negative association between maternal urinary BPA exposure and birth weight, driven by a lower birth weight in male offspring. Further research is required to explore the underlying mechanisms of BPA’s possible sex-specific associations.